Cultura alimentaria, mitos y deporte - García Fernández, Oscar; Cachán Cruz, Roberto (Estudios humanísticos. Geografía, historia y arte, 1997)
The field of food choice is reveled as an exciting area with many challenging iusses for reseach. The food choice attracks scientists from a wide variety of disciplines, such as physiology, nutrition, marketing, psychology, sociology, etc. In this paper we attemp from the anthropology and sport, so that we can show the attitudes towards feedeing, their mythes, bias, preferences and differences in social and class attitudes. Both approaches must complement each other and are totally necessary for a correct analysis of feeding and sport.